(untitled) (Sciences & Technology. A, exactes sciences, 2017)
We present a comparative theoretical study on the structural and electronic properties of Al1−xInxNalloy in both zincblende and wurtzite phases based on the semiempirical sp3s* tight binding model with nearest neighbor interactions and density functional theory with modiﬁed Becke–Johnson potential (mBJLDA). Optimizing the lattice parameters, the physical parameters such as band gap, effective mass, density of states and charge density were calculated for the entire composition range of Al1−xInxNalloy. Results of the calculations made by both theories are found to be in good agreement for both zincblende and wurtzite phases.